Modelling the Hydrologic Impacts of the Nanting River Regulation and On-site Validation in the Mengding Urban Area, China-Myanmar. Issue 2 (September 2019) - Ji, Yong-xing; Han, Fei-fei; Zhang, Jian-lin; Yin, Yue; Song, Chen
Abstract: The Nanting River runs through China and Myanmar, which has been planned to be renovated as the urban river of Mengding City, Yunnan. In order to make the river regulation works more efficient, different river discharges are tested in the 1-D and 2-D numerical models to investigate the variation of river hydrology and local flow field profiles before and after the construction works. The results are used to validate the feasibility of designed river parameters (including the width and the depth) and assess the correlation impacts. It proves that: 1) The Nanting River is a typical southern mountain river, of which the discharge has a great difference between rainy and dry seasons. The waterscape and flood control capability of different discharges should be considered for both ecological environment and flood control safety. 2) 1-D model is benchmarked against the on-site measurement data. The results indicate that 1-D model has the capability to simulate the hydrological characteristics before and after the regulation works and represent the influence of upstream and downstream flow. The results can be used as the boundary conditions in the 2-D model. 3) The simulations of the local flow field with different flow discharges are carried out by a 2-D numerical model. Those results are used for the assessments of the project layout and the revetment protection. 4) During the implementation of the regulation works, this project experienced the extreme flood which was close to the defense limit. Moreover, an earthquake and several floods hit this region. The structures survived and maintained in good condition in the hazards which proves that this regulation project is successful and necessary and the research method is valid and efficient.